Fifth Grade Students’ Logical Thinking in Mathematics - Syafitri, Rani; Putra, Zetra Hainul; Noviana, Eddy (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2020)
The purpose of this study was to investigate fifth-grade students’ logical thinking in mathematics. Their logical thinking skills were categorized based on five levels, namely very low, low, medium, high and very high. This study used descriptive quantitative method, and it was conducted with 123 fifth-grade students from a public elementary school in Pekanbaru, Riau, Indonesia. The instruments used to collect data were logical thinking ability tests consisting of short answer tasks and mathematical reasoning for the given answers. The results of this study indicated that students have very low logical thinking within the average score of 22.76%. More than half of students could not give correct answers to the given tasks and also could not provide reasoning to their answers. The implication of this study is that teachers, teacher educators, curriculum developers, and government need to develop learning instruction that support students’ logical thinking in facing challenges in 21st century life.